Mitigation strategy on reduction greenhouse gas (GHG) emission of landuse sector for the province of Papua - Suebu, Elvis Franklin; Hermana, Joni; Boedisantoso, Rachmat (Sustinere: Journal of Environment and Sustainability, 2017)
Studying the right strategy in the implementation of the mitigation of reducing GHG emission in an effort to control climate change caused by deforestation and forest degradation (REDD +) in Papua Province is an important step that must be done. Emission levels in Papua Province in 2010 was dominated by forestry sub-sector and other land use in the amount of 639,818,463 ton CO2eq or approximately 99.8% from the  total of GHG emissions of 640,737,952.64 ton CO2eq. To analyze the implementation strategy of mitigation (REDD +), the calculation of the level of carbon emission must be done first. The calculation of carbon emissions for this sub-sector is done by referring to the method that has been developed by the IPCC GL-2006. Meanwhile, to sub-sectors of forestry and other land use, the calculation used the historical and forward-looking approach. The level of carbon emissions from forestry sub-sector accounted for 921,779,031.23 ton CO2eq (historical method) and 1,052,683,205.46 ton CO2eq (forward-looking method) of mitigation program at the end of 2020. Strategy of mitigation action program was for carbon uptake and carbon storage stabilization. The mitigation scenario for forestry sub-sector capable of reducing emissions was by 552,303,873 ton CO2eq or by 52.47% of the total cumulative emissions at the end of 2020 (forward-looking method).